Pengaruh Tripton dan Arang Aktif pada Pembesaran Bibit Anggrek Phalaenopsis In Vitro - Ferziana Ferziana (Jurnal Penelitian Pertanian Terapan, 2013)
The research was aimed to discover the influence of tripton and active carbon on faster orchid Phalaenopsis in vitro seedling enlargement and to obtain the best media that will spur the enlargement of orchid Phalaenopsis in vitro seedling. The research was using completely randomized design with 8 treatments and 4 replications, and then analyzing the data by using analyze of variant that continued with 5% LSD test. The treatments of this research were : ToAo: Tripton 0 g.l-1 + without active carbon, ToA2: Tripton 0 g.l-1 + active carbon 2 g.l-1 , T1Ao: Tripton 1 g.l-1 + without active carbon, T1A2 : Tripton 1 g.l-1 + active carbon 2 g.l-1 , T2Ao: Tripton 2 g.l-1 + without active carbon, T2A2 : Tripton 2 g.l-1 + active carbon 2 g.l-1 , T3Ao: Tripton 3 g.l-1 + without active carbon, T3 A2: Tripton 3 g.l-1 + active carbon 2 g.l-1 . Basic media that used in this research was foliar fertilizer vitabloom media 2 g.l-1 given vitamin B-1 technique 1 cc.l-1, sugar 20 g.l-1 , tomatoes 60 g.l-1, agar 7 g.l-1, coconut water 150 cc.l-1. The result of this research can be concluded that (1) the influence of tripton and active carbon on orchid phaleonopsis seedling show significant effect on seedling length and the width of leaf, whereas the number of leaf , the number of root, root length and seedling wet weight were not showing significant difference, (2) Media treatment with tripton and active carbon (T1A2) is better in accelerating growth of seedling length and leaf width. Keywords: Tripton, active carbon, Seedling Enlargement,Phalaenopsis